2015
DOI: 10.1021/acs.langmuir.5b00592
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Flowerlike Gold Nanoparticles Labeled Immunochromatography Test Strip for Highly Sensitive Detection of Escherichia coli O157:H7

Abstract: Gold nanoparticles (AuNPs) labeled lateral-flow test strip immunoassay (LFTS) has been widely used in biomedical, feed/food, and environmental analysis fields. Conventional ILFS assay usually uses spherical AuNPs as labeled probes and shows low detection sensitivity, which further limits its widespread practical application. Unlike spherical AuNP used as labeled probe in conventional ILFS, in our present study, a hierarchical flowerlike AuNP specific probe was designed for LFTS and further used to detect Esche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…This effort is testified also by the number of papers reporting new materials to be used as labels [10][11][12][39][40], sometimes in combination with innovative detection technologies [13,41], and of enhancement strategies aimed at increasing the sensitivity of the ICST compared to using traditional gold nanoparticles [42][43], as also summarized in two comprehensive reviews [44][45]. Within the number of novel materials for labeling antibodies in ICTS, the request for analytical devices with multiplexing capability is prompting towards using labels easily distinguishable from each other, such as nanoparticles with different colors [19][20]23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effort is testified also by the number of papers reporting new materials to be used as labels [10][11][12][39][40], sometimes in combination with innovative detection technologies [13,41], and of enhancement strategies aimed at increasing the sensitivity of the ICST compared to using traditional gold nanoparticles [42][43], as also summarized in two comprehensive reviews [44][45]. Within the number of novel materials for labeling antibodies in ICTS, the request for analytical devices with multiplexing capability is prompting towards using labels easily distinguishable from each other, such as nanoparticles with different colors [19][20]23].…”
Section: Resultsmentioning
confidence: 99%
“…1); even if semi-quantitative tests can be designed, as well [8][9]. Besides common spherical GNPs, some authors reported the use of non-spherical [10][11] and multilayer GNPs [12][13] as labels for ICSTs with the aim of improving the assay sensitivity More specifically, Ji et al used multi-branched GNPs as labels for developing an ICST for the detection of Aflatoxin B1, and reported higher optical brightness, better colloidal stability and better sensitivity than using s-GNPs [11]. These multi-branched GNPs exhibited a blue color instead of the red color of s-GNPs, because the size and shape of GNPs have significant influences on the SPR band.…”
Section: Introductionmentioning
confidence: 99%
“…Among labels mentioned above, colloidal gold has been used in lateral flow test more than other labels (Zhao, Zhang et al 2008;Wang, Zhang et al 2009;Chen and Yang 2015;Zhang, Huang et al 2015).…”
Section: Labels For Immunochromatographic Assaysmentioning
confidence: 99%
“…Also, colloidal gold in unconjugated forms and conjugated forms can be easily found from a variety of commercial sources (Tse 2009). Besides, several investigations have been reported on the potential benefits of using different labels, for example, fluorescent dyes, liposomes encapsulating visible or fluorescent dyes, quantum dots, magnetic nanoparticles, and silver-gold nanoparticles (Goryacheva, Lenain et al 2013;Byzova, Smirnova et al 2014;Zhang, Huang et al 2015;RodrĂ­guez, CoviĂĄn et al 2016;Wu, Yuan et al 2016) A study using fluorescent immunoliposome as a label has been described by Khreich et al (Khreich, Lamourette et al 2008) for detection of Staphylococcus aureus enterotoxin B (SEB) in water and juice.…”
Section: Labels For Immunochromatographic Assaysmentioning
confidence: 99%
“…11 Compared with the other two ways, exploring the optimized label probes for LFA is a simple and effective means to improve the detection sensitivity. 11 Compared with the other two ways, exploring the optimized label probes for LFA is a simple and effective means to improve the detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%